2020
DOI: 10.47238/ijeca.v5i1.121
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effects of Preheating on Still Productivity

Abstract: Single basin solar still (SBSS) has low productivity in this experimental research, some techniques have been employed to solve this problem, these techniques consist of using a flat plate collector. The main aim of this research was to make efficient use of the flat plate collector (FPC) to increase solar still productivity, and it works as a hybrid device. The model solar water heater for the flat plat collector (FPC) was coupled with a solar still, and the tests were repeated in 3 to 5 winter days, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Numerous studies have been conducted, all of which aim to increase the productivity of pure, drinkable water that is produced from solar distillers, such as pre-heating of solar energy feeding experimentally by Badran and Tahina [13], and the use of pre-heating by means of a flat solar panel led to an improvement in the amount of water accumulated by 36%. Cherraye [14] found that integrating a solar distillation unit with a flat plate collector increased production by 87%. Abdel-Bar and Hassan [15] compared the performance of the solar distillation unit without preheating and similar solar performance with preheating the feed which was done by cooling the surface of a photovoltaic panel, the results showed that preheating the solar still feed water by 60% increases the productivity of solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted, all of which aim to increase the productivity of pure, drinkable water that is produced from solar distillers, such as pre-heating of solar energy feeding experimentally by Badran and Tahina [13], and the use of pre-heating by means of a flat solar panel led to an improvement in the amount of water accumulated by 36%. Cherraye [14] found that integrating a solar distillation unit with a flat plate collector increased production by 87%. Abdel-Bar and Hassan [15] compared the performance of the solar distillation unit without preheating and similar solar performance with preheating the feed which was done by cooling the surface of a photovoltaic panel, the results showed that preheating the solar still feed water by 60% increases the productivity of solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…Preheating the feed of solar still was experimentally tested by Badran and Al-Tahaineh [24], the preheating was achieved by a solar flat plate, and it was found that preheating improved the amount of water accumulated by 36%. Cherraye [25] found that integrating solar still with one flat plate collector increased production by 87%. Abd Elbar and Hassan [26] compared the performance of a solar still without preheating and a similar solar still with feed preheating which was done by cooling a photovoltaic panel surface, the results had shown that preheating the solar still feed water by 60% increase the productivity of the solar still, the energy efficiency, the exergy efficiency by 20.9%, 20%, and 60.64%, respectively.…”
Section: Introductionmentioning
confidence: 99%